Synthesis and characterizations of absorbent dressing turmeric extract curcumin chitosan-alginate hydrogen and ZnO nano for mediate and high exudation - Astuti, Amin; Hendrarti, Wahyu; Wunas, Jenny (Annals of Mechnikov's Institute, 2019)
This study carried out the test of the effectiveness of Hydrogel formula of turmeric extract - chitosan and ZnO nano for wound in Oryctolagus cuniculus, New Zealand rabbits, using Sodium alginate as a hydrogel agent. It was done to obtain a physically stable formula made from turmeric - chitosan and ZnO nano Hydrogel extracts to heal a wound. The stable hydrogels were tested further in vivo with three New Zealand rabbits and divided into three treatment groups, are stable Hydrogel preparations, positive controls, and negative controls. The results showed that stable hydrogel of chitosan turmeric extract and ZnO nano were effective to heal the wound as marked by a reduction in wound diameter faster than wound diameter in negative control rabbits. Further in the Anova test with a Complete Randomized Design (CRD) data obtained F count value of 596 > F table 1% 10.92. Indeed, there is a very significant difference between the three treatment groups. Additionally, the result of Tukey's HSD (honestly significant difference) test obtained that from the three treatment groups has a significantly different effect with negative control and not significantly different from positive control; preparations that have been known to have a healing effect on wound.